Kadar Air, Kadar Protein dan Organoleptik Bakso Ayam Petelur Afkir Pada Proporsi Tepung Ceker Ayam Berbeda - Afrila, Akhadiyah; Handayani, Sri; Karter, Bastianus Jimi (Universitas Muhammadiyah Gorontalo, 2025)
The purpose of this study was to measure the effect of flour and chicken feet on the water quality, protein, and organoleptic properties of leftover chicken meatballs. This study was conducted using a completely randomised design (CRD) at the Industrial Engineering and Microbiology Laboratory of TribhuwanaTunggadewi University, Malang. In detail, the treatments were given as P0 (100 percent chicken meat without chicken feet flour), P1 (95 percent chicken meat and 5 percent chicken feet flour), P2 (90 percent chicken meat and 10 percent chicken feet flour), and P3 (85percent chicken meat and 15 percent chicken feet flour). The data obtained were tested organoleptic using the ChiSquare (X²) approach and analysis of variance (ANOVA) to determine the relationship between variables. Then the Least Significant Difference (LSD) test was carried out at the 5% level. The results showed that the addition of chicken feet flour to meatballs did not change their water content. The addition of chicken feet flour had a major impact on protein content; however, the best treatment in P3 (85% chicken meat and 15% chicken feet flour) had the highest protein value (0.63).In contrast, the P0 treatment containing only chicken meat had the lowest protein value (0.31). According to the research findings, the addition of chicken feet flour increased the protein content of leftover laying hen meatballs, with P3 as the ideal amount. This research opens up opportunities for the development of healthier and more nutritious meatball products, as well as optimizing the use of raw materials that are often considered waste, such as chicken feetTujuan penelitian ini adalah untuk mengukur pengaruh tepung ceker ayam dan daging ayam petelurafkir terhadap kualitas air, protein, dan organoleptik bakso ayam petelur afkir. Penelitian ini dilakukan dengan menggunakan rancangan acak lengkap (RAL) di Laboratorium Rekayaasa Proses Industri Universitas Tribhuwana Tunggadewi Malang. Perlakuan terdiri dari 4 yaituP0 (100 persen daging ayam tanpa tepung ceker), P1 (95 persen daging ayam dan 5 persen tepung ceker), P2 (90 persen daging ayam dan 10 persen tepung ceker), dan P3 (85 persen daging ayam dan 15 persen tepung ceker). Data yang diperoleh dilakukan uji organoleptik dengan menggunakan pendekatan Chi- Square (X2) dan analisis variansi (ANOVA) untuk mengetahui hubungan antar variabel.Bila terdapat perbedaan dilanjutkan Uji Beda Nyata Terkecil (BNT) pada taraf 5% . Hasil penelitian menunjukkan bahwa penambahan tepung ceker ayam ke dalam bakso tidak berpengaruh terhadap kadar air. Penambahan tepung ceker ayam berpengaruh terhadap kadar protein dimana perlakuan P3 (15% tepung ceker ayam dan 85% daging ayam ) menghasilkan nilai protein tertinggi (0,63). Penambahan tepung ceker ayam meningkatkan kadar protein bakso ayam petelur afkir, dengan P3 sebagai jumlah ideal. Penelitian ini membuka peluang untuk pengembangan produk bakso yang lebih sehat dan bernilai gizi tinggi, serta mengoptimalkan pemanfaatan bahan baku yang sering dianggap sampah, seperti ceker ayam